The Evolution and Geometry of the Outer Parts of the Small Magellanic Cloud. - Hatzidimitriou, D. (Ph.D. Thesis, 1989)
Available from UMI in association with The British Library. Requires signed TDF. The purpose of this study is to achieve an improved and more complete understanding of the structure and evolutionary history of the Small Magellanic Cloud, the second nearest galaxy to our own. The study was focused on the northeastern and west/southwestern outer parts of the SMC, including populations at projected distances larger than 2.2 kpc from the centre of the SMC. These regions have scarcely been studied in detail in the past. The observational material consisted of good quality B and R photographic plates taken with the U.K. Schmidt Telescope in Australia, digitised by the COSMOS automatic microdensitometer and calibrated by a series of CCD photometric sequences obtained at the European Southern Observatory (with the 1.5m Danish Telescope) and at the Anglo-Australian Observatory (with the 4m Telescope). Colour-magnitude diagrams were constructed over the whole of the area measured. The analysis of the properties of these diagrams resulted in (a) establishing the population synthesis in the outer parts of the SMC as a function of position with respect to the centre, and (b) probing the geometrical structure (in three dimensions) of these outlying regions of the SMC, which led to the discovery of a significant line-of-sight depth in the NE outer parts. A study of the carbon star population in the SMC outer regions was also conducted, using UKST prism plates. The carbon stars were used as probes of the intermediate-age populations in the outer parts of the SMC.
Keywords: Astrophysics; Calibrating; CARBON STARS; Charge Coupled Devices; Color-Magnitude Diagram; Distance; Galactic Structure; Magellanic Clouds; Microdensitometers; Observatories; Photographic Plates; Photometry; Physics: Astronomy and Astrophysics; Prisms; Schmidt Telescopes; Sequencing; Stellar Color; Stellar Magnitude